Collaboration between local government and related stakeholders in the child friendly district program in Cirebon regency - Rakhmat Hardiyansyah (Journal of Law Science, 2024)
Indonesia has a child friendly regency/city program which is a collaborative development system that guarantees the fulfillment of children's rights and special protection for children. The problem is that collaboration in child-friendly districts in Cirebon Regency has not been running optimally, this can be seen from the evaluation results of child-friendly districts in each cluster of child-friendly districts. Stakeholders have not implemented commitment programs and programs together, so there is a need for governance in their implementation. This research aims to increase collaboration in realizing a child-friendly district in Cirebon Regency. This research uses qualitative methods with primary and secondary data collection. Data collection techniques in this research used primary data, secondary data, observation, interviews, literature study and documentation. The results of the research show that cooperation is good but not optimal in implementing communication and commitment to implementing child-friendly district programs. Several problems can be seen from budget limitations, coordination between institutions and lack of commitment to program sustainability. Therefore, to increase collaboration, local governments and stakeholders need commitment, communication and budget support in activity programs so that they can be accommodated well.